(untitled) (American Journal of Islam and Society, 2003)
The Islamic world underwent profound political and religious changes in the eleventh and twelfth centuries. These changes were paralleled by one of the most significant transformations of Islamic art and architecture. What shared meaning lies at the origins of these two historical developments? How, if at all, were these paralleled transformations part of the same struggle? The Transformation of Islamic Art during the Sunni Revival takes us into this dialogue. This work consists of seven chapters, including a plethora of beautiful photographs, in which Yasser Tabbaa, a professor at the University of Michigan and a highly regarded Islamic art scholar, argues that the transformations in medieval Islamic architecture and ornament during this period reflected and embodied the conflict between the ‘Abbasid and Fatimid dynasties. It is in the struggle for political authority and religious legitimacy that new and competing forms of expression took hold. In discussing the book’s themes and the discourses of which it is a part, Tabbaa refutes the essentialist traditions of some Orientalists, art historians, and even aestheticians that, while having seemingly different intentions, all portray Islamic art as separate or divorced from its history. They ignore or gloss over significant historical developments in the Islamic world, and therefore represent Islamic art, in all of its variety, as a homogenous genre, as the term arabesque implies. Tabbaa highlights the epoch of the Sunni revival by rejecting the essentialist models and focusing on the period’s unique conflicts and changes. He argues that calligraphic, ornamental, and architectural forms, in addition to being instruments of perceptual mediation, were engendered within specific discourses to give symbolic support to certain claims to authority and to establish a difference against challenging claims ...